Characterization of toxic gas effluents of a Philippine-manufactured Polypropylene product in bench-scale experiments - Daliposa, Karl Patrick Tatunay; Tambo, Kenji Cate Canlas; Pacheco, Benito M.; Aquino, Diocel Harold M. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Fire Safety Engineering is concerned about reducing the risk of losses to both life and property by applying necessary engineering tools and concepts in the prevention and mitigation of the detrimental effects of fire. The assessment of the toxicity of materials during fire is one of the concerns of this relatively new field of engineering. In the Philippines, Polypropylene is a common material used for house wares, furniture, and food packaging. However, further experimentation to determine its toxicity in fire should be carried out in order to aid the assessment of its safety. Through the use of the UK Defence Standard 02-713 and the UP ICE Toxicity Chamber, the toxic gas effluents of Polypropylene under well-ventilated, flaming conditions were determined. It was found that this material yields an index lower than other common materials in the industry including untreated wood (TI ≤ 2.5), Polyurethane (TI = 12.4), and Polyethylene (TI = 18.2). The calculated toxicity index of Polypropylene passed that general product standard of 2.5 set by the UK Defence - Standard 07-247 by having a calculated Toxicity Index of 2.0.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Polypropylene -- Toxicity testing